Precision requirements for the POLLUX-LUVOIR spectropolarimeter - Muslimov, Eduard; Bouret, Jean-Claude; Neiner, Coralie; Ferrari, Marc; Lombardo, Simona; Lopez Ariste, Arturo; Le Gal, Maëlle (SPIE, 2020)
POLLUX is a project of high-resolution UV spectropolarimeter for the prospective LUVOIR space observatory. It will work in the range of 90-400 nm with R ≥ 120000. The baseline design consists of 3 channels representing echelle spectrographs with dedicated polarimeters, customized echelles and freeform-based concave holographic gratings. We study the requirements for manufacturing and assembly precision. We consider three performance criteria related to the spectral resolving power, calibration stability, and the gratings diffraction efficiency. We perform the tolerance analysis in corresponding modes using raytracing and numerical methods of diffraction modelling in a Monte-Carlo loop. We emphasize the most influential design parameters, which may require high precision of manufacturing and alignment and should be the subjects of further studies. We also briefly discuss possible compensators for maintenance of the imaging performance.